Understanding staff development - Webb, Graham (Buckingham : The Society for Research into Higher Education and Open University Press, 1996)
Introduction. Positive knowledge and progress in staff development. Staff development for understanding people and ourselves. To critically go. Postmodernity and staff development. By diverse paths...
Keywords: College teaching; College teachers; College teaching; College teachers -- Training of